Educação infantil em tempo integral nos municípios de Serra e Vila Velha : os planos municipais em destaque - Oliveira, Telmy Lopes de (2016)
This study analyzes the challenges facing the implementation process of the Full time Early Children’s Education, in the light of the new Municipal Education Plans in two cities considered the most populous ones in the Metropolitan Region of Greater Victoria (RMGV): Vila Velha and Serra. This research establishes as its objectives to identify how the organization and implementation of the educational policy in those full time schools within the municipal education departments are made; and it also aims to examine the strategies adopted by these municipalities for the realization of that process. This is a qualitative research, of an exploratory nature, whose data collection was made through semi-structured interviews and the analysis of official documents. The subjects were the coordinators of the Early Children’s Education Management (GEI) of the Municipal Departments of Education and the presidents of the Municipal Councils. This work tries to understand how the municipalities are organizing the implementation of Full Time Early Childhood Education from their Municipal Education Plans. With the survey results discrepancies with regard to the care of the nursery and pre-school are perceived and, therefore, the effectiveness of the strategies that deal with early children’s education become a major challenge, especially when the search for the expansion of early children’s education does not articulate with other public demands of the first stage of basic education. Despite the new prerogatives contained in the Municipal Education Plans, the expansion and the provision of full time early children’s education do not constitute a priority in the municipalities studied, since their respective Departments of Education are looking for, in principle, ensuring a compulsory and free preschool for children aged four (4) to five (5) years old. Given that the National Education Plan (PNE), Law No. 13,005 / July 13th 2014, is a planning tool of Espírito Santo State that guides the implementation and improvement of educational policies, hence we can conclude that the implementation of the PNE (2014-2024) demands some efforts to overcome this challenge that ,since the Constitution of 1988, the field of education has been facing, namely, the realization of the right to education of young children. Finally, this research highlights that to understand how children and their livelihoods are being considered in this process that ends up legislating the offering of full time early children’s education is very important for future studies..